Preparation of Ammonium Phosphotungstate Composite Loaded with Silica-calcium Alginate Hybrid Material and Its Adsorption Performance for Cs+ - DIAO Xinya1, 2, FAN Ye1, 2, HAO Lecun1, 2, ZHAO Xin1, 2, JIN Qiang1, 2, , CHEN Zongyuan1, 2, GUO Zhijun1, 2, (Yuanzineng kexue jishu)
The separation and extraction of radioactive cesium is of great significance for the safe disposal of high-level liquid waste (HLLW). Although ammonium phosphotungstate (AWP) has shown notable selectivity for Cs+ adsorption in HLLW, the micro-crystalline structure and fine powder morphology of AWP limit its industrial application with column separation. Therefore, it is important to prepare AWP-based adsorbents into a usable form to improve their utilization. In this paper, a novel millimeter-sized AWP-based adsorbent, AWP-CaALG-SiO2 composite, was prepared by encapsulating the fine crystals of AWP exchanger into a calcium alginate-silica matrix. The prepared composite was characterized using scanning electron microscopy (SEM), Fourier transform infrared (FT-IR) spectra, X-ray fluorescence (XRF), X-ray diffraction (XRD), N2 adsorption/desorption isotherms and the universal testing machine, and its adsorption performance for Cs+ in strong acidic solution was determined using both batch-type and dynamic column experiments in terms of the kinetics, equilibrium capacity and selectivity. The characterization results indicate that the addition of silica in the fabrication significantly improves the mechanical strength of composite in comparison to those without silica. The adsorption of Cs+ on AWP-CaALG-SiO2 composite could reach equilibrium within 12 h, and the adsorption kinetics follows a non-linear pseudo-second order rate equation. The distribution coefficient of Cs+ is high even in extreme acidic condition (about 150 mL/g in 8.0 mol/L HNO3 solution). The adsorption capacity of Cs+ increases significantly with the increase of initial Cs+ concentration, and the adsorption of Cs+ on AWP-CaALG-SiO2 composite can be well fitted with the Langmuir model, indicating a homogeneous single-layer adsorption process. The maximum adsorption capacity of AWP-CaALG-SiO2 composite for Cs+ is determined to be 22.9 mg/g with batch-type experiment in 3.0 mol/L HNO3 solution. In addition, the composite shows excellent selectivity toward Cs+ uptake over 8 co-existing metal ions in simulated HLLW, as evidenced by a Kd value of 772 mL/g and SF values all above 42. The dynamic column experiment shows that the composite can serve as the stationary phase in columns to effectively remove Cs+ with the maximum dynamic adsorption capacity of 17.3 mg/g. This work not only develops a granulated AWP-based composite for the selective capture of Cs+ from strongly acidic HLLW, but also provids insights into the design of high-mechanical strength ion-exchange materials for radiocesium decontamination with their practical applications.